Synthesis and classical pathway Complement inhibitory activity of C7-functionalized filifolinol derivatives, inspired in K-76 COOH - Larghi, Enrique Leandro (2012)
A series of carboxylic acids carrying various functionalization on C-7 of their common 3H-spiro[benzofuran-2,1?-cyclohexane] skeleton were synthesized from filifolinol, as analogs of the natural Complement inhibitor K76-COOH. In order to probe the relevance of the C-7 functionalization on their bioactivity, the ability of the analogs to inhibit Complement activation through the classical pathway was determined. The observed results suggest that functionalization of C-7 can modulate the inhibitory activity of the tested compounds. The 7-trifluoromethyl derivative was the compound with the lowest IC50 value among the tested analogs, being more potent than K76-COOH.